Development of LPFG-Based Seawater Concentration Monitoring Sensors Packaged by BFRP - Zhe Zhang; Tongchun Qin; Yuping Bao; Jianping He (Micromachines)
Leveraging the sensitivity of long-period fiber grating (LPFG) to changes in the environmental refractive index, an LPFG-based seawater concentration monitoring sensor is proposed. Considering the highly saltine and alkali characteristics of the sensor’s operating environment, the proposed sensor is packaged by basalt fiber-reinforced polymer (BFRP), and the sensor’s sensitivities were studied by sodium chloride and calcium chloride solution concentration experiments and one real-time sodium chloride solution concentration monitoring experiment. The test results show the wavelength of LPFG, a 3 dB bandwidth and a peak loss of LPFG’s spectrogram change with changes in the concentration of sodium chloride or calcium chloride solutions, but only the wavelength has a good linear relationship with the change in solution concentration, and the sensing coefficient is −0.160 nm/% in the sodium chloride solution and −0.225 nm/% in the calcium chloride solution. The real-time monitoring test further verified the sensor’s sensing performance, with an absolute measurement error of less than 1.8%. The BFRP packaged sensor has good corrosion resistance and a simple structure, and it has a certain application value in the monitoring of salinity in the marine environment and coastal soil.